Rancang Bangun Sistem Informasi Pengaduan Masyarakat pada Kecamatan Dolok Masihul - Monika Rodearni Damanik; Gortap Lumbantoruan; Eviyanti Novita Purba (Universitas Methodist Indonesia, 2024)
Dolok Masihul District is one of the districts in Serdang Bedagai Regency, North Sumatra. In delivering public services, Dolok Masihul District still uses a manual system for handling public complaints. This results in a lack of transparency, efficiency, and effectiveness in the complaint handling process. Therefore, a community complaint information system is needed to facilitate the process of submitting, monitoring, and reporting complaints. This research aims to design and build a community complaint information system for Dolok Masihul District. The information system is developed using PHP programming language and MySQL database. The outcome of this research is a community complaint information system that can receive complaints, monitor the status of complaints, and generate complaint reports. System testing shows that the system operates effectively and meets user needs.